2022
DOI: 10.1007/s43032-022-00999-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming in Animal Models: Critical Evidence of Current Environmental Negative Changes

Abstract: The Developmental Origins of Health and Disease (DOHaD) approach answers questions surrounding the early events suffered by the mother during reproductive stages that can either partially or permanently influence the developmental programming of children, predisposing them to be either healthy or exhibit negative health outcomes in adulthood. Globally, vulnerable populations tend to present high obesity rates, including among school-age children and women of reproductive age. In addition, adults suffer from hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 227 publications
(220 reference statements)
0
6
0
Order By: Relevance
“…Several mechanisms underlying fetal programming have been examined in preclinical, e.g. [121,122] and human perinatal stress research. We refer to [73 ▪▪ ,123] for recent overviews.…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...mentioning
confidence: 99%
“…Several mechanisms underlying fetal programming have been examined in preclinical, e.g. [121,122] and human perinatal stress research. We refer to [73 ▪▪ ,123] for recent overviews.…”
Section: Perinatal Mental Health and Offspring Outcome: Results Mecha...mentioning
confidence: 99%
“…For example, dietary factors during pregnancy, such as overnutrition or malnutrition, severely affect the risk of the offspring developing a metabolic disease or CVD during later life [ [527] , [528] , [529] ]. This also holds true for noise pollution, which affects the risk of disease in human and animal offspring via prenatal epigenetic reprogramming [ 530 ].…”
Section: Pathophysiological Mechanisms Of Noise Exposurementioning
confidence: 99%
“…Preterm birth, preeclampsia, and small-for-gestational age (SGA) are the adverse outcomes of exposure to smog air pollutants ( Figure 5 ). SGA is described as infants with a weight less than 10% at a specified gestational age ( 37 ). Previous study showed that the incidence of preterm birth and pre-eclampsia were 4.4 and 2.7% respectively in pregnant women upon long term exposure to smog air, especially ozone.…”
Section: Endocrine Disruptive Effects Of Gaseous Constituents Of Smogmentioning
confidence: 99%